Peningkatan Kemampuan Berpikir Kritis Siswa Menggunakan Hyflex Learning Berbantuan Wordwall - Maulina Zaidatul Ma’rifah; Mawardi Mawardi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2022)
The dullness of online learning has an impact on the decline of critical thinking skills and student learning outcomes. These problems can be solved through action research with the aim of improving students' critical thinking skills and learning outcomes using the Hyflex learning design assisted by Wordwall. This action research uses the Stringer model, including the look, think and act stages. The research subjects were all 5th grade students of SD Negeri 1 Saban, Gubug District, Grobogan Regency, a total of 37 students. The research was carried out in March-April in the second semester of the 2021/2022 academic year. The research instrument used an observation sheet to obtain information on learning activities, a rubric for measuring students' critical thinking skills, and a test to measure student learning outcomes. The data analysis technique used percentation, categorical, and comparative techniques. The results of the action research show the following findings: 1) students' critical thinking skills have increased, with a difference in the average score of students' critical thinking skills from Cycle I to Cycle II of 10.29 points; 2) the average student learning outcomes have increased, with the difference in scores from Cycle I to Cycle II of 4.5 points. While the percentage of completeness of classical learning outcomes has increased, with a percentage difference of 24.31%.